PENGARUH SALES GROWTH, CURRENT RATIO, FIRM SIZE, DAN RETURN ON ASSETS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Herna Sari Dewi; Andri Tampubolon; Angel Rika; Thomas Handoko; Enda Noviyanti Simorangkir; Hottua Samosir (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
Capital structure is permanent financing consisting of long-term debt, preferred stock and stockholders's equity. Companies in determining the capital structure needs to consider and pay attention to the many variables that influence directly for capital structure decisions will affect the condition and value of the company and to determine the company's ability to survive and thrive. The research is used a quantitative research approach. This type of research is used quantitative research and the nature of this research is causal relation research. The research samples is used purposive sampling technique consisting of 25 consumer goods companies. The research simultaneously showed that sales growth, current ratio, firm size, and return on assets had a significant effect on capital structure of consumer goods companies listed on the Indonesia Stock Exchange for the period 2012-2016. The research partially showed that sales growth did not have any significant effect on capital structure, current ratio and return on assets had negative and significant effect on capital structure, and firm size had positive and significant effect on capital structure.